Protocol to image deuterated propofol in living rat neurons using multimodal stimulated Raman scattering microscopy - Wenying Zhong; Robert Oda; Yasuyuki Ozeki; Masato Yasui; Mutsuo Nuriya (STAR Protocols, 2023)
Summary: Propofol is a widely used anesthetic important in clinics, but like many other bioactive molecules, it is too small to be tagged and visualized by fluorescent dyes. Here, we present a protocol to visualize deuterated propofol in living rat neurons using stimulated Raman scattering (SRS) microscopy with carbon-deuterium bonds serving as a Raman tag. We describe the preparation and culture of rat neurons, followed by optimization of the SRS system. We then detail neuron loading and real-time imaging of anesthesia dynamics.For complete details on the use and execution of this protocol, please refer to Oda et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.